Karabalgasun und Karakorum, Mongolei - Franken, Christina (e-Forschungsberichte des DAI, 2023)
The KAAK has conducted excavations in the old Mongolian capital Karakorum (founded 1220/35 AD) since 2000, complemented by excavations in the Uyghurian capital Karabalgasun (740‒840 AD) since 2007. Both cities are situated near to each other in the Orkhonvalley about 370 km in the west of the todays Mongolian capital Ulaanbaatar. In 2012/2013, the archaeological research mainly focused on the architectural details of the citadel in the southeast of the so-called palatial or temple complex as well as on the question of continuity of the gate situation in Karakorum.